What Triggers Caldera Ring‐Fault Subsidence at Ambrym Volcano? Insights From the 2015 Dike Intrusion and Eruption. Issue 6 (2nd June 2021) - Shreve, T.; Grandin, R.; Smittarello, D.; Cayol, V.; Pinel, V.; Boichu, M.; Morishita, Y.
Abstract: Surface deformation accompanying dike intrusions is dominated by uplift and horizontal motion directly related to the intrusions. In some cases, it includes subsidence due to associated magma reservoir deflation. When reservoir deflation is large enough, it can form, or reactivate preexisting, caldera ring‐faults. Ring‐fault reactivation, however, is rarely observed during moderate‐sized eruptions. On February 21, 2015 at Ambrym volcano in Vanuatu, a basaltic dike intrusion produced more than 1 m of coeruptive uplift, as measured by InSAR, synthetic aperture radar correlation, and Multiple Aperture Interferometry. Here, we show that an average of ∼40 cm of slip occurred on a normal caldera ring‐fault during this moderate‐sized (VEI < 3) event, which intruded a volume of ∼24 × 10 6  m 3 and erupted ∼9.3 × 10 6  m 3 of lava (DRE). Using the 3D Mixed Boundary Element Method, we explore the stress change imposed by the opening dike and the depressurizing reservoir on a passive, frictionless fault. Normal fault slip is promoted when stress is transferred from a depressurizing reservoir beneath one of Ambrym's main craters. After estimating magma compressibility, we provide an upper bound on the critical fraction ( f  = 7%) of magma extracted from the reservoir to trigger fault slip. We infer that broad basaltic calderas may form in part by hundreds of subsidence episodes no greater than a few meters, as a result of magma extraction from the reservoir during moderate‐sized dike intrusions. Plain Language Summary: Many volcanoes feature large depressions, called calderas. Calderas form when enough magma leaves a deep reservoir, and the solid rock lid above this reservoir can no longer support its own weight. Caldera faults, or cracks surrounding the reservoir which extend from the reservoir to Earth's surface, form as the lid collapses. Ambrym volcano (Vanuatu) has a 12‐km wide caldera, and researchers propose it formed during an explosive eruption 2, 000 years ago. However, in 2018, Ambrym's caldera sunk along caldera faults during a nonexplosive eruption. This observation questions whether an explosive eruption was necessary to form Ambrym's caldera in the first place. Furthermore, in February 2015, an eruption 10 times smaller than in 2018 also caused the ground to sink along caldera faults. Utilizing ground motion data obtained from satellite radar systems to model magma reservoir outflow and fault displacement, we conclude that, in 2015, the ground sank along caldera faults. This sinking is explained by the removal of as little as <7% of the stored magma from the reservoir. We therefore propose that Ambrym's wide caldera may have formed as a result of many frequently occurring medium‐sized eruptions. This challenges the thought that wide calderas mainly form as a result of large eruptions. Key Points: Ground displacement at Ambrym in February 2015 was caused by a dike intrusion, deflating reservoir, and normal slip on a caldera ring‐fault Extracting at most 7% of the magma from Ambrym's reservoir suffices to reactivate the caldera ring‐faults Normal slip along Ambrym's ring‐fault can occur during moderate‐sized eruptions, resulting in subsidence and further caldera development